(untitled) (Research, Society and Development, 2021)
Objective: to evaluate the implementation and observed effects of the Strategy Breastfeed and Feed Brazil (SBFB) in Health Units (HU) in Piracicaba/SP. Methods: evaluative research carried out in two stages: 1) analysis of teams’ adherence to SBFB; 2) comparative analysis of food consumption markers in HUs with and without SBFB. In step 1, data were obtained by an instrument for monitoring the actions agree in the SBFB implementation workshops and, in step 2, by food consumption markers registered in the Food and Nutrition Surveillance System for the period from 2015 to 2018. Results: In step 1, 100% of the HUs had 80-85% adherence by the team and agreed on actions to promote breasteeding and healthy complementary feeding. In step 2, HUs with SBFB showed an increase in the average percentage of exclusive breastfeeding indicators in children under 6 months, complementary breastfeeding, introduction of food and a reduction in the instant noodles consumption indicator. Conclusion: There was good adherence to SBFB by the team members and the indicators for promoting of breastfeeding and healthy complementary feeding of the HUs with SBFB were more positive than those without SBFB.